Comparison between inverted and unprocessed digitized radiographic imaging in periodontal bone loss measurements - Scaf, Gulnara [UNESP]; Morihisa, Olívia; Loffredo, Leonor de Castro Monteiro [UNESP] (FapUNIFESP (SciELO), 2007)
The advances in digital imaging technology in dentistry have provided an alternative to film-based radiography and have given new options to detect periodontal bone loss. The purpose of this study was to compare inverted and unprocessed digitized radiographic imaging in periodontal bone loss measurements. Thirty-five film-based periapical radiographs of patients suffering from moderate to advanced untreated periodontal bone loss associated to lower premolar and molars was selected from the department files, with 40 bone loss areas. The film-based radiographs were digitized with a flatbed scanner with a transparency and radiograph adapter used for transilluminating the radiograph imaging. Digitization was performed at 600 dpi and in gray scale. The images were digitized using Image Tool software by applying image inversion, that is, transformation of radiopaque structures into radiolucent structures and vice-versa. The digital data were saved as JPEG files. The images were displayed on a 15-inch and 24-bit video monitor under reduced room lighting. One calibrated examiner performed all radiographic measurements, three times, from the cementoenamel junction to the most apical extension of the bone loss, in both types of image (inverted and unprocessed). Brightness and contrast were adjusted according to the examiner's individual demand. Intraclass correlation coefficient was used to compare the measurements from both types of images. The means of radiographic measurements, in mm, for inverted and unprocessed digitized imaging were 6.4485 and 6.3790, respectively. The intraclass correlation coefficient was significant (0.99) The inverted and unprocessed digitized radiographic images were reliable and there was no difference in the diagnostic accuracy between these images regarding periodontal bone loss measurements.
Keywords: Bone loss/diagnosis; Digital processing; Radiography, dental